The Compounding Effect: How Co-Offending Exacerbates the Harm Caused by Violent Offenders - Piper, Emily (American journal of criminal justice, 2024)
To what extent do violent offenders cause harm to victims when they act independently versus when they collaborate with others? Currently, it remains unclear whether co-offending exacerbates the degree of violence, partly due to measurement considerations, i.e. how to account for varying degrees of crime severity. Using police records from Dorset, UK, we compare violent crimes committed by lone individuals to those committed by co-offending networks using a crime harm index. While lone offenders commit the majority of violent acts, those with multiple connections to other violent offenders yielded higher average and total harm scores. Moreover, the severity of offences is proportional to the scale of the criminal network, with larger violent networks linked to higher crime harm scores. Finally, the propensity for recidivism is greater among co-offender groups compared to lone offenders. The implications of the compounding effect of co-offending on violence are discussed.